Forensic Evaluation of Injury Pattern in Pedestrian Road Traffic Accidents in Karachi: Forensic Evaluation in Pedestrian Road Traffic Accidents - Waheed, Abdul; Khan, Iqbal Ahmed; Khan, Farzana Azam; Qayyum, Sadia Abdul; Ram, Hari; Nadeemuddin, Muhammad (Pakistan Journal of Health Sciences, 2025)
Pedestrian-related injuries are among the top of all road traffic-related injuries in Pakistan. Objectives: To determine the pattern of injuries and responsible factors for pedestrian fatality due to road traffic accidents in Karachi. Methods: This retrospective study was carried out at the Department of Forensic Medicine, Karachi Institute of Medical Sciences. Victims involved in pedestrian road traffic accident fatalities, belonging to either gender of any age from three major hospitals in Karachi, were evaluated. Information was recorded in a semi-structured written questionnaire. The multivariate logistic regression analysis was performed for multiple variables simultaneously and reports adjusted odds ratios to determine the independent contribution of each factor to pedestrian mortality. A p-value less than 0.05 was considered statistically significant. Results: A total of 681 deceased pedestrians were examined and evaluated for the patterns and factors. The majority of the deceased were male (81.0%) with a mean age of 34.7 ± 2.9 years. The highest proportion (39.2%) of fatalities due to RTA was reported in the 18-30 years’ age group. Over two-thirds (74.6%) of accidents took place on the main roads of the city. Common injuries that resulted in death included fatal injuries to the brain and associated vessels (64.4%) and thoracic injuries (14.7%). Conclusion: The findings highlight a significant prevalence of male victims, particularly in the 18-30 age group, with brain injuries being the leading cause of death. The analysis also emphasizes the critical role of accident timing, with peak fatalities occurring between 12:00 pm and 4:00 pm, and on main roads.